Juridical Review of Electronic Medical Records as Therapeutic Evidence in Health Law Practice - Nasution, Erdi Effendi; Siregar, Abdul Rahman Maulana (Formosa Journal of Applied Sciences, 2025)
One important innovation that has emerged is the use of Electronic Medical Records (RME), which serves to record, store, and manage patient medical data digitally, replacing the conventional paper-based medical record system. The utilization of RME provides many advantages, such as efficiency, data accuracy, and faster access to medical information. In addition to improving the quality of health services, RME also has the potential to become valid evidence in legal procedures, especially in disputes related to medical malpractice. However, the use of RME as evidence in a legal context poses various challenges, especially regarding the validity and authenticity of the data. Therefore, a juridical study on the application of RME in medical practice is needed in order to meet applicable legal standards, provide protection for patients' rights, and ensure that this technology is used legally in legal proceedings.